2015
DOI: 10.1108/srj-09-2013-0114
|View full text |Cite
|
Sign up to set email alerts
|

SME stakeholder relationship descriptions in website CSR communications

Abstract: The aim of this paper is to report on an exploratory, qualitative study of how small and medium enterprises (SMEs) describe their firm's relationships with or impact on stakeholders when communicating corporate social responsibility (CSR) on their websites. Design/methodology/approach: Qualitative content analysis was conducted on 22 Australian SME websites from the information media and telecommunications sector. Stakeholder theory was used as the basis for analysis. Findings: An important aspect of CSR commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…The descriptive statistics reveal that the SE score connected to nonfinancial reports and websites were 37%, 63%, and 32.34%, respectively, highlighting the substantial coincidence between the content presented in each. Furthermore, according to Parker, Bellucci, Zutshi, Torlina, and Fraunholz (), the SE score connected to websites reveals that firms still paid little attention to their stakeholders in CSR communication (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The descriptive statistics reveal that the SE score connected to nonfinancial reports and websites were 37%, 63%, and 32.34%, respectively, highlighting the substantial coincidence between the content presented in each. Furthermore, according to Parker, Bellucci, Zutshi, Torlina, and Fraunholz (), the SE score connected to websites reveals that firms still paid little attention to their stakeholders in CSR communication (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The third most common theme among CSRS research was CSR communication (9.7%). These articles revealed that CSR communication among SMEs is low (Dincer & Dincer, 2010;Parker et al, 2015;O'Connor et al, 2017). The reasons for the low level of CSR communication were revealed as: fear of criticism, lack of proper management skills and resources (Dincer & Dincer, 2010).…”
Section: Csrs Research Themesmentioning
confidence: 99%
“…Few studies to date have researched CSR reporting on SME websites. For example, Parker et al (2015) studied the portrayal of stakeholder relationships in website CSR communications among a sample of 22 Australian media SMEs, some of which included CSR-type initiatives on their websites. Even where CSR communication does exist, they note a reluctance to highlight CSR as a way of developing market share or indeed as a ‘business issue’.…”
Section: Explicit and Implicit Csr Communicationmentioning
confidence: 99%